Peningkatan Hasil Belajar Mata Pelajaran Fiqih Melalui Penerapan Metode PQRST (Preview, Question, Read, Summarize, Test)Peserta Didik Kelas V Di Mi Ismaria Al-Qur’aniyah Islamiyah Raja Basa Bandar Lampung Tahun Pelajaran 2016/2017”. - Hasanah, Uswatun (Universitas Islam Negeri Raden Intan Lampung, 2017)
The purpose of the study was to determine whether the application of the PQRST method can improve the learning outcomes of students in Class V MI. This research is Classroom Action Research (CAR) because in class action research can study learning problems in the classroom through reflection to solve problems by doing planned actions in real situations and analyzing each influence of the treatment. Data collection methods used are the method of observation, interviews, documentation, and tests. The sample in this study is class V students of Ismaria Al-Qur'aniyyah Islamiyah Raja Basa Bandar Lampung 2016/2017. This research was conducted in two cycles. Cycle I with the material Knowing Halal Food and Drinks, cycle II consists of Knowing Food and Beverages. Based on the results of the study, it was concluded that through the application of the PQRST method (Preview, Question, Read, Summarize and Test) can improve the learning outcomes of fiqh subjects in fifth grade students in MI 2016/2017 academic year.